Prevalência de xerostomia em mulheres durante a quimioterapia por câncer de mama - Pinto, Vania Lopes [UNIFESP] (2020)
Objective: to identify the prevalence of xerostomia in women diagnosed with breast cancer and undergoing chemotherapy treatment in a public reference service in the city of São Paulo. Method: prospective cohort with women diagnosed with any malignant breast cancer, with or without previous surgical procedure and / or previous chemotherapy, in outpatient care. Women who discontinued or abandoned treatment during the data collection period, those who changed their treatment to non-chemotherapy, and those who needed a regimen with more than 16 sessions were excluded only the surpluses. The sample calculation predicted an expected error of 17% at an expected prevalence of 50% and with a significance level of 95% therefore considered a sample of 27 women followed up at the end of treatment. The research respected all stages of study with human beings, including obtaining the signature of the Informed Consent Form and submitting it to the Research Ethics Committee. Data collection was performed using two instruments built by the researchers to identify the sample characterization data and anamnesis of the oral cavity. The identification of dry mouth was assessed by means of a validated xerostomia evaluation questionnaire cross-culturally adapted to the Portuguese language, which was applied before the beginning of treatment and after each administration of chemotherapy. Results: All women in the study were from the State of São Paulo aged 35 to 77 years and with an average of nine years of schooling. Dry mouth complaints were present in 48.1% of women before chemotherapy and they were 28 times more likely to develop xerostomia during treatment. It was observed that the use of antiemetics contributed to the increased occurrence of xerostomia and the antiulcerants presented as a protective factor. Conclusion: the present study identified the prevalence of xerostomia in the studied population of 75.4%.